Telomere Roles in Fungal Genome Evolution and Adaptation - Rahnama, Mostafa; Wang, Baohua; Dostart, Jane; Novikova, Olga; Yackzan, Daniel; Yackzan, Andrew; Bruss, Haley; Baker, Maray; Jacob, Haven; Zhang, Xiaofei; Lamb, April; Stewart, Alex; et al. (Frontiers in Genetics, 2021)
Telomeres form the ends of linear chromosomes and usually comprise protein complexes that bind to simple repeated sequence motifs that are added to the 3’ ends of DNA by the telomerase reverse transcriptase (TERT). One of the primary functions attributed to telomeres is to solve the “end-replication problem” which, if left unaddressed, would cause gradual, inexorable attrition of sequences from the chromosome ends and, eventually, loss of viability. Telomere-binding proteins also protect the chromosome from 5’ and 3’ exonuclease action, and disguise the chromosome ends from the double-strand break machinery whose illegitimate action potentially generates catastrophic chromosome aberrations. Telomeres are of special interest in the blast fungus, Pyricularia, because the adjacent regions are enriched in genes controlling interactions with host plants, and the chromosome ends show enhanced polymorphism and genetic instability. Previously, we showed that telomere instability in some P. oryzae strains is caused by novel retrotransposons (MoTeRs) that insert in telomere repeats, generating interstitial telomere sequences that drive frequent, break-induced rearrangements. Here, we sought to gain further insight on telomeric involvement in shaping Pyricularia genome architecture by characterizing sequence polymorphisms at chromosome ends, and surrounding internalized MoTeR loci (relics) and interstitial telomere repeats. This provided evidence that telomere dynamics have played historical, and likely ongoing, roles in shaping the Pyricularia genome. We further demonstrate that even telomeres lacking MoTeR insertions are poorly preserved, such that the telomere-adjacent sequences exhibit frequent presence/absence polymorphism, as well as exchanges with the genome interior. Using TERT knockout experiments, we characterized chromosomal responses to failed telomere maintenance which suggested that much of the MoTeR relic /interstitial telomere associated polymorphism could be driven by compromised telomere function. Finally, we describe three possible examples of a phenomenon known as “Adaptive Telomere Failure,” where spontaneous losses of telomere maintenance drive rapid accumulation of sequence polymorphism with possible adaptive advantages. Together, our data suggest that telomere maintenance is frequently compromised in Pyricularia but the chromosome alterations resulting from telomere failure are not as catastrophic as prior research would predict, and may, in fact, be potent drivers of adaptive polymorphism